A REVIEW: EXPLORING GENETIC VARIATION AND REGULATORY NETWORKS IN WHEAT HEAT STRESS TOLERANCE - ULLAH , I; MAJEED , HN; BATOOL , R; FAROOQ, S; GULAB , R; HABIBA , SU (Biological and Clinical Sciences Research Journal, 2024)
Wheat (Triticum aestivum L.) is a staple crop vital to global food security, yet rising global temperatures increasingly threaten its productivity. Heat stress (HS), particularly during critical growth phases like anthesis, disrupts physiological and biochemical processes, reducing yields and grain quality. This review explores the genetic variation and regulatory mechanisms that underpin wheat’s resilience to heat stress. Advanced breeding techniques, such as genome-wide association studies (GWAS), quantitative trait loci (QTL) mapping, and next-generation sequencing, have identified key genetic factors contributing to heat tolerance. Novel biotechnological strategies, including CRISPR/Cas9 gene editing, have shown promise in introducing heat-tolerant traits by targeting specific genes. Additionally, omics approaches encompassing transcriptomics, proteomics, and metabolomics offer deeper insights into stress-responsive pathways. With machine learning and artificial intelligence integration, wheat breeding is poised to become more efficient, accelerating the development of cultivars capable of withstanding heat stress. These advancements are essential to ensure sustainable wheat production amidst the challenges of climate change.